(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
We analyze the combined influence of activation energy,Brownian motion,thermophopresis, past a stretching sheet with variable viscosity and thermal radiation. The governing equations have been solved by employing fifthorder Runge-Kutta-Fehlberg method along with shooting technique. The effects of various parameterson the velocity, temperature and concentration as well as on the local skin-friction coefficient, local Nusselt number and local Sherwood number are presented graphically and discussed. It is observed that a velocities components increase with Hall parameter(m), Brownian motion parameter(Nb), Radiation parameter(Rd), Viscosity parameter ( r), Convective heat transfer constant(h1), reduces with thermophoresis parameter(Nt). Nusselt number increase in r and reduces Nu and Sh, increase in r/h1 reduces rate of heat transfer and enhances mass transfer.